Accuracy of 3‐Dimensional Sonography for Diagnosis and Classification of Congenital Uterine Anomalies. (1st June 2013) - Moini, Ashraf; Mohammadi, Sedigheh; Hosseini, Reihaneh; Eslami, Bita; Ahmadi, Firoozeh
Abstract : Objectives: Congenital abnormalities of the müllerian ducts are not very common, yet they contribute to the problem of infertility. The purpose of this study was to determine the sensitivity and specificity of 3‐dimensional (3D) sonography for diagnosis of congenital uterine abnormalities. Methods: This study was performed in 214 women with fertility problems who were suspected to have müllerian anomalies at Arash Hospital from April 2010 to April 2011. All patients underwent 3D sonography to assess for uterine anomalies during the luteal phase of the spontaneous cycle. Sonography was performed by one radiologist, after which one surgeon performed a hysteroscopy and a laparoscopy in each of the patients while under general anesthesia. The 3D sonographic results were not available to the surgeon. Finally, the results were compared to determine the sensitivity, specificity, and accuracy of 3D sonography. Results: Final evaluations of 204 patients showed uterine anomalies in 84.3% of the patients. For diagnosis of uterine anomalies, the sensitivity of 3D sonography was 86.6%, and specificity was 96.9%. The positive predictive value was 99.3%, and the negative predictive value was 54.4%, with an 88.2% accuracy rate. For classification, the positive predictive value of 3D sonography was 82.3%, and accuracy was 76%; without short septa and arcuate uteri, accuracy was 95%. Conclusions: It seems that 3D sonography has a high level of accuracy for most uterine anomalies. In the case of an arcuate uterus and short septa, more precision and increased experience will improve accuracy.